Penerapan Yoga Brahmari Pranayama untuk Mengontrol Risiko Perilaku Kekerasan pada Pasien Skizofrenia di RSJ Ratumbuysang Sulut - Ningrum, Puspita; Purwanti, Erna; Alhalawi, Zikri; G. Aseng, Christina (Universitas Nurul Jadid, 2025)
Background: The risk of violent behavior is one of the problems of schizophrenia which is characterized by disturbances in the thought process, perception, emotional responses, and social interactions. Yoga Brahmari Pranayama is a calming pranayama technique that involves making a humming sound when exhaling which aims to provide calm, reduce anxiety, and reduce stress. The purpose of this case study is to get an overview of the application of Yoga Brahmari Pranayama as a control in schizophrenia patients with nursing problems of the risk of violent behavior. The case study was conducted at Prof. Dr. V.L. Ratumbuysang Mental Hospital in the Kabela and Cakalele rooms. The method used is descriptive using a case study approach. The measuring instrument used in this study was an observation sheet of signs and symptoms of the risk of violent behavior. Results: After doing Yoga Therapy, the results obtained were that the patient was calmer, more relaxed and there was a decrease in signs of violent behavior. Conclusion Yoga Brahmari Pranayama as a companion therapy in patients with the risk of violent behavior is useful for controlling emotions and reducing violence. Suggestions Nurses can use Yoga Brahmari Pranayama therapy as a companion therapy in schizophrenia patients with nursing problems of the risk of violent behavior.